THE USE OF DEVICES IN E-LEARNING AS A SOURCE OF LITERATURE AT SMKN 1 BAKUNG - Dian Tri Riska Ekawati; Mutmainnah Mustofa; Saiyidi Hasbullah (Prominent, 2022)
The Covid-19 epidemic, which started in Wuhan, China in 2019, has spread to a number of countries, including Indonesia. Learning from Home is another term for online learning (BDR). To show support for government policies and to assist students in meeting their educational needs, SMKN 1 Bakung adopts an online learning strategy using e-learning. The aim of this article is to show many types of literature and the use of devices in e-learning as a source of literature. Qualitative research is used for this research. After analyzing the data, it could be concluded that in e-learning SMKN 1 Bakung, there are some types of works of literature. They are separated based on their characteristics and locations. Due to the characteristic, they are textual, non-textual, and mixed documents. While based on the location, they are general and references collections. The literature is mostly in form of pdf to make them easily accessed by students. The use of devices in e-learning is as follows: accessing courses, accessing exams/tests as well as accessing teleconference.